The Aesthetic Functionality of the Pictorial Composition for the Musical Film (Al-Academy, 2023)
The cinematic film is a pictorial structure that depends on composition as its basis through the functional role that it plays in the process of building the cinematic image, starting with the plastic aspects, passing through the elements of the pictorial language. Therefore, the researcher studies the basic principles of the term aesthetic and its preoccupations in the motion picture arts, by identifying the preoccupations of composition. In all the aesthetic aspects of the musical cinematic film by means of the vision and artistic style of the creator of the work, and the modalities of constructing the cinematic image to express the aesthetic message represented by the dramatic artistic idea, and then studying the aesthetic sensory image through which the aesthetics of the cinematic image are created at the levels of form and content. artistic.This is done by studying the concept of the concept of (work) through the constructive relationship that operates between composition as a visual concept and the directorial process of the cinematic image, and dealing with the visual plastic construction of the cinematic image in order to construct the meaning (content), to address the topic of the structural work of the image in the cinematic film through elements The formal language, which finally combines to create a formative aesthetic for the formal structure in the musical cinematic film